Nilai Nilai Kearifan Lokal Generasi Millenial di Kota Banjarmasin - Husna Husna; Maudi Indriani; Mukarromah Mukarromah; Restu Khaliq (UIN Antasari Banjarmasin, 2022)
Abstract: The Banjar people are the original inhabitants of the Banjar tribe who mostly occupy the province of South Kalimantan. Distinctiveness lies in the language, traditions, culinary and many other uniqueness. This research was conducted based on references from various journals and interviews. This research was conducted with the aim of finding out what are the views or opinions of the millennial generation regarding the values of local wisdom in the Banjar community. Nowadays, there are many paradigms about science and modern technology that have influenced the decline of local wisdom values. Therefore, we as the next generation strive to build, explore and preserve the values of the local wisdom of the nation and tribe so that they are maintained and not lost to the times.